Design of a media agenda in Cuba in response to the challenges faced by the Juventud Rebelde newspaper from the revolutionary left in the context of the Covid-19 pandemic and new geopolitical variations - Guanche Ledesma, Raciel; Pineda Mirabal, Rosmery (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
The present research aims to describe the variations in the process of construction of the media agenda in the Cuban newspaper Juventud Rebelde during the pandemic stage due to Covid-19 in the period 2020-2022. Through a triangulated analysis between the broadcasting contexts, the practices related to the creative work and the characteristics that distinguished the production in the selected time. It also seeks to demonstrate new communicative practices used to convey messages in accordance with the media’s policy to the public, and the challenges that this period entailed in the fields of politics and public policies from the revolutionary left. The work leads to the critical reflection and reverts results to the institutional direction of Juventud Rebelde newspaper that, presumably, will be able to use these data for the present and future decisions in the work of the media.